2016
DOI: 10.1097/shk.0000000000000624
|View full text |Cite
|
Sign up to set email alerts
|

An Intravenous Bolus of Epa

Abstract: In this rat model of myocardial IR, an intravenous Omega-3 bolus before reperfusion decreases IR-induced vascular failure and shock. These results open therapeutic perspectives as far as myocardial reperfusion process is concerned that deserve further explorations in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…Supplementation with the DHA diet diminished the superoxide anion levels near to control levels, similar to those reported in the aorta of these animals [24]. In line with these results, is the ability of n-3 PUFAs to decrease superoxide anion production in mouse aorta [38] and human fibroblasts [39]. In addition, DHA has been reported to decrease oxidative stress in vascular [40], nervous [41] and immune [42] systems.…”
Section: Discussionsupporting
confidence: 75%
“…Supplementation with the DHA diet diminished the superoxide anion levels near to control levels, similar to those reported in the aorta of these animals [24]. In line with these results, is the ability of n-3 PUFAs to decrease superoxide anion production in mouse aorta [38] and human fibroblasts [39]. In addition, DHA has been reported to decrease oxidative stress in vascular [40], nervous [41] and immune [42] systems.…”
Section: Discussionsupporting
confidence: 75%
“…These data suggest that DHA pretreatment has physiological consequences on the development of MI-induced LV dysfunction, preserving cardiac function in mice. The observed DHA-induced attenuation of MI-induced LV dysfunction adds to cardioprotective effects of other omega-3 FA in a Langendorff perfusion model reporting that an intravenous bolus of EPA: DHA 6: 1 protects against myocardial ischemia-reperfusion-induced injury [ 23 ]. Furthermore, preserved LV function in DHA-pretreated mice 14 days after MI is in line with the clinical data from the OMEGA-REMODEL trial, demonstrating that in humans, the combination of DHA and EPA ω -3 FA ethyl ester supplementation beginning after the onset of STEMI improved LV function after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, supplementation is recommended for patients with prevalent CHD such as a recent MI [ 21 , 22 ]. DHA is either obtained from diet but can also be synthesized from EPA [ 23 , 24 ]. Thus, various investigations used combinations of DHA and EPA to investigate ω -3 FA effects on cardiac health.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, many animal studies have shown that n-3 PUFAs might have good effects on MI/R injury. In a rat model of acute MI/R, intravenous injection of n-3 PUFAs before reperfusion reduced vascular failure and shock caused by I/R (35). A diet rich in n-3 PUFA from fish oil affected heart function and improved cardiac responses to I/R via reducing oxygen consumption and increasing post-ischemic recovery (36).…”
Section: Discussionmentioning
confidence: 99%